Becoming Western: A Postcolonial Reading of Jun'ichirō Tanizaki's Naomi - Iqbal, Mukhammad (2016)
A novel represents a lot of meanings. Naomi is a novel which portrays westernization in 1920's Japan. This study attempts to analyze the issue of mimicry in a central character, Naomi, in Junichiro Tanizaki'sNaomi and how mimicry affects the characterization in the process of character development. To investigate mimicry in this novel, this study employed a qualitative method which focuses on providing the portrait of Naomi, and her transformation on becoming westernized modern girl. The analysis began by identifying ambivalence from Naomi's practice of mimicry, then, categorizing the ambivalence based on the meanings. The analysis reveals that the process of mimicry acted by Naomi can be seen in four aspects: physical resemblance, materialism and consumerism, intelligence, and etiquette. The findings suggest that mimicry shapes Naomi into an in-between moga (modern girl) that is caught between two cultures, Japanese and Western cultures, as evidenced in her ways of being and acting. From the analysis, it can be concluded that Naomi is a representation of Japanese's moga or modern girl who mimics the Westerners' way of acting, but fails to be equal with Westerners in their way of being.;--- Sebuah novel merepresentasikanbanyakmakna.Naomi adalah novel yang menggambarkanwesternisasi di Jepangpadatahun 1920.Penelitianinimencobamenganalisisisumengenaimimkripadakaraktersentral, Naomi, dalam novel Naomi yang ditulisoleh Junichiro Tan'izaki and bagaimanamimikrimemengaruhi proses pengembangankarakternya. Untukmenelitimimikri, penelitianinimenggunakanmetodekualitatif yang berfokuspadapenggambaran Naomi danperubahannyasaatterkenadampakwesternisasimenjadigadismoderen.Analisisdimulaidenganmengidentifikasiambivalensidaripraktikmimikri yang dilakukan Naomi, lalu, mengkategorikanmimikritersebutberdasarkanmaknanya.Hasilanalisismenunjukanbahwa proses mimkri yang dilakukan Naomi bisadilhatdalamempataspek, yaitu: kemiripanfisik, materialism dankonsumerisme, kepandaian, danetika. Hasilpenelitianmenunjukanbahwamimikrimembentuk Naomi menjadimoga(gadismoderen) "in-between" (berlawanan) yang terjebak di antaraduabudaya, Jepangdan Barat, yang dibuktikanmelaluicaranyaberlakudanbertingkah. Dari analisistersebut, dapatdisimpulkanbahwa Naomi adalahrepresentasigadis modern Jepangataumoga yang dengansempuradalammenirucara orang-orang Barat bertingkah, namungagaluntukmenyamaicarauntukmenjadi orang-orang Barat.